Aportes del enfoque territorial y diferencial en la construcción de una política pública de telesalud en Colombia (2020)
The discussion of the design of telehealth public policies is necessary in a country like Colombia, due to the progressive construction of a legislative framework that adds up technological progress in public health as far that it is implemented. In Colombia, despite of legislative progress on the topic, the desired or expected impact has not been generated, since the services being offered have been inequitable focused on urban or centralized areas of the country. That is why in this work was proposed to develop contributions from a territorial and differential approach to the construction of a telehealth public policy. To achieve this, a bibliographic review, information gathering and subsequent analysis were performed in order to nourish the possibilities provided by the differential and territorial approaches in the implementation of health public policies, and especially telehealth, these allow us to recognize priorities in law-related to health by understanding the unequal development between regions and their population, thereby making the search for solutions to the problems of each territory more effective. The contributions of the territorial and differential approaches to formulation of public policies and technological advances in healthcare sector open up the way in the reflection on the actions carried forward by the State, giving it tools and mechanisms to overcome inequity and exclusion in Colombian healthcare.